Factors Behind The Relapse Of The Patients With Alcohol And Opioid Use Disorder: An Exploratory Study - Geetesh Kumar Singh, Ayoleena Roy, Aratrika Roy, Thiyam Kiran Singh, M.V.R. Raju (International Journal of Advanced Science and Technology, 2020)
Background: Among the psychoactive drugs, alcohol and opioid are the most used and misused ones, which lead to serious socio-occupational dysfunction in one’s life. The most troublesome part is, despite excessive control and treatment, the relapse of the patients with alcohol and opioid use disorder seems to be inevitable. Methods and Material:The purpose of the study is to understand and to have an in-depth information about the reasons behind the relapse of the patient with alcohol and opioid use disorder. A qualitative study conducted on a sample of 20 participantsage between 25 - 60 from Psychiatry OPD, who diagnosed with alcohol or opioid use disorder and had relapsed after being abstinent. They telephonicallycontacted and interviewed based on a predetermined open-ended interview schedule. The information obtained from the interviewee, coded based on thematic analysis method and so the themes were analyzed. Results: Among patients with ‘Opioid Use Disorders’ the main factors leading to relapse were found to be increased physiological craving, poor self-control and desire to indulge in entertainment which involves opioid consumption. On the other hand, among patients with ‘Alcohol Use Disorder,’ coping skill strategy at the time of stress and environmental triggers like sight of the usual places of alcohol consumption found to be the main factors. While physiological craving and influence of peer group found to be existed in both the groups. Conclusion: The major factors behind the relapse in the patients with alcohol and opioid use disorder are physiological craving, peer pressure and family stressors. Poor coping were found to be the precipitation factor of Alcohol use disorder whereas physical craving and poor self control were the precipitation factors of Opioid use disorder.